Getting to Know the Various Forms of Business Organizations and Expansion Strategies that Entrepreneurs Must Understand - Adik Ayu; azizatun niswah; naila radha soraya; Nunuk Indarti (International Journal of Technology and Education Research, 2026)
Understanding the forms of business organizations and expansion strategies is essential for entrepreneurs who aim to achieve sustainable growth. Each type of business organization sole proprietorship, partnership, corporation, cooperative, and state-owned enterprise has unique characteristics that influence managerial structure, risk distribution, capital acquisition, and the company’s potential for expansion. Additionally, expansion strategies, both internal and external, play a crucial role in increasing market reach and competitive advantage. This article identifies various business organization forms, analyzes factors that influence organizational choice, and explains the expansion strategies relevant to different business types. The findings highlight the importance of aligning organizational structure with expansion strategies to optimize business growth in a competitive environment.